The influence of college students’ social networks on entrepreneurial opportunity recognition in Hebei Province, China - Ma, Jiao; Chang, Yuan-Cheng (Edelweiss Applied Science and Technology, 2025)
This study aims to explore how social networks and resilience predict entrepreneurial opportunity recognition among university students in entrepreneurship-focused universities in Hebei Province, China. The goal is to provide insights for innovation and entrepreneurship management decisions in local universities. Using a convenience sampling method, a questionnaire survey was conducted with 466 valid responses collected. The results show that social networks have a significant positive impact on entrepreneurial opportunity recognition, and resilience plays a mediating role in this relationship. Therefore, it is important to place special emphasis on developing resilience among student entrepreneurs.